2022
DOI: 10.1186/s12883-022-02736-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of background EEG activity based on MRI findings in neonatal hypoxic-ischemic encephalopathy: a standardized, low-resolution, brain electromagnetic tomography (sLORETA) study

Abstract: Background It is important to assess the degree of brain injury and predict long-term outcomes in neonates diagnosed with hypoxic-ischemic encephalopathy (HIE). However, routine studies, including magnetic resonance imaging (MRI) and conventional encephalography (EEG) or amplitude-integrated EEG (aEEG), have their own limitations in terms of availability and accuracy of evaluation. Recently, quantitative EEG (qEEG) has been shown to improve the predictive reliability of neonatal HIE and has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Similarly, the study by Nash et al [23] also distinguished three types of background EEG activity: improved activity in 49% of neonates, unchanged ac-tivity in 38% of neonates, and worsened activity in 13% of neonates. Other investigators have reported changes in background EEG activity in neonates during TH [25] [37]. The duration and severity of cerebral anoxia, the location, extent, and number of cerebral lesions could explain the occurrence of the 3 types of background EEG activity [38]- [44].…”
Section: Discussionmentioning
confidence: 90%
“…Similarly, the study by Nash et al [23] also distinguished three types of background EEG activity: improved activity in 49% of neonates, unchanged ac-tivity in 38% of neonates, and worsened activity in 13% of neonates. Other investigators have reported changes in background EEG activity in neonates during TH [25] [37]. The duration and severity of cerebral anoxia, the location, extent, and number of cerebral lesions could explain the occurrence of the 3 types of background EEG activity [38]- [44].…”
Section: Discussionmentioning
confidence: 90%
“…55 Spectral analysis incorporating spatial distribution of changes has recently demonstrated that changes in the temporal lobes may be particularly predictive. 56 Similarly, functional connectivity, a quantitative measure of the functional connection between brain regions, which is impossible to assess on visual review of the raw EEG, has been associated with outcomes in to severe NE. 57 Overall, these findings support that the excitotoxicity and metabolic stress of hypoxicischemic injury leads to abnormal neurovascular regulation and impairment in functional connectivity, with some regions of the growing brain being particularly vulnerable to injury.…”
Section: Quantitative Eeg In Ne Neuroprognosticationmentioning
confidence: 99%
“…Similar techniques were applied prospectively to 36 neonates with hypoxic–ischemic encephalopathy, and determined measurements of poor neurovascular coupling had an AUC of 80% for predicting brain MRI abnormalities 55 . Spectral analysis incorporating spatial distribution of changes has recently demonstrated that changes in the temporal lobes may be particularly predictive 56 . Similarly, functional connectivity, a quantitative measure of the functional connection between brain regions, which is impossible to assess on visual review of the raw EEG, has been associated with outcomes in moderate to severe NE 57 .…”
Section: Quantitative Eeg In Ne Neuroprognosticationmentioning
confidence: 99%
“…Brain activity studies have explored the correlation effects with the BDNF. Theta and beta power positively correlate with serum BDNF levels in the right temporoparietal region in gambling disorder ( Kim et al, 2022 ). Brain connectivity areas involved in pain processing, particularly functional connectivity between the thalamic subregions with the PFC, have been found to be associated with BDNF in individuals with long-term primary dysmenorrhea ( Han et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…It uses a three-dimensional head model and EEG recordings to estimate electrical activity in different brain regions. This method was validated through correlations with other imaging techniques, such as functional magnetic resonance imaging (fMRI) and MRI ( Mulert et al, 2004 ; Kim et al, 2022 ). Despite the use of a limited number of electrodes, sLORETA has provided valuable insights into the underlying sources of brain activity ( Michel and Brunet, 2019 ).…”
Section: Introductionmentioning
confidence: 99%